Prenatal exposure to finasteride promotes sex-specific changes in gerbil prostate development - Maldarine, Juliana S.; Sanches, Bruno D. A.; Cabral, Ágata S. [UNESP]; Lima, Maria L. D. [UNESP]; Guerra, Luiz H. A. [UNESP]; Baraldi, Carolina M. B. [UNESP]; Calmon, Marília F. [UNESP]; Rahal, Paula [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (CSIRO Publishing, 2019)
Finasteride is a drug that is widely used in the treatment of benign prostatic hyperplasia, hair loss and even as a chemotherapeutic agent in the treatment of prostatic adenocarcinoma. However, its use is known to cause several side effects in adults and it can also cause changes in the embryonic development of the male prostate, which is a cause for concern given the possibility of the accumulation of finasteride in the environment. Nevertheless, no studies have investigated the effects of finasteride on the development of the prostate in females, which occurs in several species of mammals. To evaluate the effects of intrauterine exposure to finasteride (500 μg kg-1 day-1) on postnatal prostate development in the Mongolian gerbil in the present study, we used immunohistochemistry, immunofluorescence, serological analysis and three-dimensional reconstruction techniques. Differences were observed in the effects of finasteride on periductal smooth muscle and cell proliferation between the sexes, as well as intersex differences in the presence of the androgen receptor, which was elevated in males, and the oestrogen receptor ERα, which was increased in females. Together, the data indicate that the female prostate has its own hormone dynamics and that there are sex-specific differences in the way in which the female prostate reacts to prenatal exposure to finasteride.
Keywords: androgen receptor; intrauterine exposure; oestrogen receptor ERα; smooth muscle